1875 Va. Acts 109, ch. 100, § 12 - (:unkn) unknown (General Publisher, 1875)
If any person shall, at any time, either in the night or day-time, shoot at wild fowl in any county bordering . . . with any gun which cannot be conveniently discharged from the shoulder at arm’s length without a rest, or have such gun in his possession on a boat, a justice of any such county shall require such gun to be surrendered, and shall order it to be destroyed, and shall fine the offender ten dollars.
Keywords: HUNTING